Mengidentifikasi Kecakapan High Order Thinking Skills (HOTS) Siswa SMA Negeri 3 Yogyakarta melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) - Efvinggo Fasya Jaya. SP (Edunusa: Journal of Economics and Business Education, 2021)
This study aims to identify the skills of students through the application of the PBL learning model in economic subjects, specialization materials, at SMA Negeri 3 Yogyakarta. This research is a quantitative research design with descriptive verification research using a survey approach. The sample in this study was probably 47 students. This study found the results that the PBL learning model affected HOTS skills in economic subjects, specialization materials, at SMA Negeri 3 Yogyakarta with a contribution of 73.3%, while the researchers saw that 26.7% of the variables studied were by other variables that were not studied.